2013
DOI: 10.1080/09603123.2013.769201
|View full text |Cite
|
Sign up to set email alerts
|

Water quality indicators: bacteria, coliphages, enteric viruses

Abstract: Water quality through the presence of pathogenic enteric microorganisms may affect human health. Coliform bacteria, Escherichia coli and coliphages are normally used as indicators of water quality. However, the presence of above-mentioned indicators do not always suggest the presence of human enteric viruses. It is important to study human enteric viruses in water. Human enteric viruses can tolerate fluctuating environmental conditions and survive in the environment for long periods of time becoming causal age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 170 publications
0
60
0
13
Order By: Relevance
“…Sin embargo, presentan limitaciones, ya que no determinan si la partícula detectada es infecciosa o no (13). Para determinar el potencial infeccioso de los virus es necesario su aislamiento en cultivos celulares, pero se desconocen las condiciones en que muchos patógenos entéricos deben ser cultivados (37), en tanto que otros virus crecen lentamente o no producen un efecto citopático (38).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, presentan limitaciones, ya que no determinan si la partícula detectada es infecciosa o no (13). Para determinar el potencial infeccioso de los virus es necesario su aislamiento en cultivos celulares, pero se desconocen las condiciones en que muchos patógenos entéricos deben ser cultivados (37), en tanto que otros virus crecen lentamente o no producen un efecto citopático (38).…”
Section: Discussionunclassified
“…Además, la dosis infeccciosa es baja (varía entre 1 x 10 1 y 1 x 10 2 ) y, por lo tanto, la presencia de un número reducido de virus puede producir enfermedades en un individuo vulnerable (1,(11)(12). La carga de mortalidad y morbilidad que se le atribuye a los agentes virales se desconoce por la poca información disponible debido a las dificultades para la recuperación y la concentración de los virus, y a los altos costos de las metodologías empleadas para el diagnóstico (13).…”
unclassified
“…Moreover, infectious viruses have been recovered at critical levels from surface waters that have met FIB impairment criteria (15). Therefore, for human infectious viruses, other types of indicators with preferred characteristics, depending on the application, will be required (9,(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…However, the presence of above-mentioned indicators do not always suggest the presence of human enteric viruses which may be more resistance than the bacterial indicators. Therefore, Lin and Ganesh, (2013) concluded that it is highly important to study human enteric viruses in water to avoid their pathogenic action on children and immunecompromised people. While the current study demonstrated the efficiency and efficacy of the two water treatment systems in removing all microbial and undesired chemical contaminants.…”
Section: Resultsmentioning
confidence: 99%